Professional training of future rhythm and choreography teachers for preschool and primary education - Petro Koval (Vasyl Stefanyk Precarpathian National University, 2017)
The article reveals the importance of training teachers of preschool and primary education by the rhythm and choreography, described the importance of choreographic art in the harmonious development of the child and the training of future teachers to such activities, the main components of rhythmic classes and choreography. Key words: professional training, harmonious development, choreography, rhythm and choreography